Study of Bio-Coal Briquette as Solid Fuel for Aluminum Smelter - Diah K. Pratiwi; Riman Sipahutar; Amir Arifin (Sriwijaya Journal of Environment, 2017)
Research on alternative energy today based on issues of global warming and greenhouse effects. The use of coal briquettes from low-calorie coal derived from mines in the province of South Sumatera originally destined for the food industry is less desirable because it emits black and smelly smoke, is difficult to turn on, and it is difficult to shut down quickly. So the thought arises to use this coal briquettes for the manufacturing industry and metal casting. In a previous study, the manufacture of mixed briquettes between low calorie coal (lignite) and biomass was more environmentally friendly due to low sulfur content. Therefore, in this study, a study was conducted to find the best biomass species to be mixed with lignite to bio-coal with the highest carbon content criteria and lowest sulfur content. The results showed that the mixture type between coconut shell and lignite reached the optimum condition with carbon content of 57.923% and the lowest sulfur was 0.259% in the mixture ratio of 9 : 1. The combustion temperature reaches 1500 K at furnace efficiency of 48%.Keywords: bio-coal briquettes; lignite. coconut shell; enthalpy difference; carbon and sulfur content; flame temperature;